LITHUANIAN DIAGNOSTICS OF LAGGING TERRITORIES: EVALUATION AND INSIGHTS - H. Meyers, William; Kairytė, Emilija; Ribašauskienė, Erika (Economics of Agriculture, 2018)
During the period 2006-2007 diagnostics were conducted on territorial aspects of rural Lithuania with a special focus on the rural areas lagging behind. The study includes analysis of economic, demographic and social indicators of rural areas at a disaggregated level and a methodology enabling the assessment of opportunities and constraints and the comparisons of rural areas in various territories. The study objective is an improved set of diagnostics that captures territorial differences, improves the targeting of RDP measures and strengthens the framework for allocation and access to structural and rural development funds. The paper discusses diagnostic methods by reviewing concepts of rurality and presenting methods used for identifying and ranking leading and lagging territories. We use selected socio-economic indicators to describe differences among municipalities in Lithuania and identify the key factors that indicate more and less successful areas. These are then used to identify and rank leading and lagging municipalities with a development index.